Inconsistencies within attachment teaching practice in Zimbabwe: call for a participatory model - Chikunda, Charles (Mentoring & Tutoring: Partnership in Learning, 2021)
This article raises some inconsistencies observed in attachment teaching practice in Zimbabwe. The argument made is that these inconsistencies are caused by the different philosophical approaches informing attachment teaching practice and its delivery, which is largely visible in teaching practice supervision. The discussion shows that while attachment teaching practice is based on social constructivism and socially critical orientations, its delivery still operates under the guise of the neoclassical instrumentalist view of education. The author proposes the participatory attachment teaching practice model as a way of trying to realign the delivery to suit the philosophical base of attachment teaching practice in initial teacher education in Zimbabwe.